The Role of Village Government in the Enviromental Restoration After Sidoarjo Mudflow Disaster: Peran Pemerintah Desa dalam Pemulihan Lingkungan Pasca Bencana Lumpur Sidoarjo - Mursyidah, Lailul; Agustina, Isna Fitria; Sukmana, Hendra (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
The Sidoarjo Mudflow disaster is an event of hot mud eruption that has heavy metal components that can pollute the soil, resulting in reduced soil fertility in areas near the Sidoarjo Mudflow disaster. The Sidoarjo Mudflow disaster has had a wide impact on the socio-economic life of residents and business activities in the surrounding area due to the damage to the environmental ecosystem after the disaster. The purpose of this study is to describe the role of the Ketapang village government in restoring the environmental ecosystem after the Sidoarjo mudflow disaster. This study uses a qualitative descriptive approach with data analysis techniques using interactive models including data collection, data reduction, data analysis and drawing conclusions. The results of this study indicate that the Ketapang village government has played a role as a stabilizer, innovator, modernizer, pioneer, and implementer itself in development activities by involving various parties including village officials, traditional leaders, students, Babinsa, Babinkamtibmas and the Sidoarjo Regency Environmental and Sanitation Service (DLHK).